Measurement Accuracy of Foot Arcus in Children Aged 8-12 years: Mobile Application vs Goniometer - Nurhidayah, Rahma Dani; Naufal , Adnan Faris (Jurnal Kesehatan, 2025)
Foot arch deformities are common in school-aged children and may interfere with posture and lower-limb biomechanics if left undetected. Preliminary observations at Madrasah Ibtidaiyah Muhammadiyah Gonilan indicated that several students showed signs of decreased medial longitudinal arch, suggesting the presence of foot arch abnormalities in the school environment. This study aimed to evaluate the accuracy of a mobile application compared to a conventional goniometer in measuring the Clarke angle. This quantitative research used a cross-sectional design with a population of 150 students aged 8–12 years. A total of 109 children were recruited using nonprobability purposive sampling, based on predetermined inclusion and exclusion criteria. Clarke angle measurements were taken using two instruments: the Quick Angle Physio mobile application and a standard goniometer. Data were analyzed using Spearman correlation because the measurement data were not normally distributed. The results showed a strong and significant correlation between the mobile application and the goniometer measurements (r=0.964–0.989, p<0.001). These findings indicate that the mobile application provides accurate measurements comparable to the conventional method. The mobile application may serve as an efficient and practical alternative for Clarke angle assessment, supporting early detection of foot arch abnormalities among school-aged children, particularly in school settings such as Madrasah Ibtidaiyah Muhammadiyah Gonilan.